Pelaksanaan Pembelajaran Menggunakan Model Pembelajaran PJBL pada Materi Teks Eksplanasi di SMPN 2 Indramayu - Zulfi Rosita; Imas Juidah; Agus Nasihin; Yayah Kurniyah (Jurnal Pendidikan Educandum, 2025)
This study aims to describe the effectiveness of implementing the Project-Based Learning (PjBL) method in improving the ability to write explanatory texts among Grade IX D students at SMP Negeri 2 Indramayu. The research focuses on the influence and impact of the PjBL learning method in the teaching and learning process. The Project-Based Learning (PjBL) method was implemented through several stages: planning, topic selection, project design, implementation, presentation of results, and evaluation. This study employed a descriptive qualitative approach, with data collection techniques including observation, documentation, and analysis of students' project outcomes. The results indicate that the implementation of PjBL successfully increased students' active participation, creativity, and critical thinking skills. The final products, in the form of explanatory texts and educational videos, showed improvements in the quality of students' writing and their understanding of the structure and linguistic features of explanatory texts. The students’ final scores mostly fell into the “good” category, with an average success rate of 75%. Therefore, the PjBL model is proven to be effective in developing 21st-century literacy skills, which include critical thinking, communication, collaboration, and creativity.